Bacteriophage: A new therapeutic player to combat neutrophilic inflammation in chronic airway diseases - Laucirica, Daniel R.; Stick, Stephen M.; Garratt, Luke W.; Kicic, Anthony (Frontiers in Medicine, 2022)
Persistent respiratory bacterial infections are a clinical burden in several chronic inflammatory airway diseases and are often associated with neutrophil infiltration into the lungs. Following recruitment, dysregulated neutrophil effector functions such as increased granule release and formation of neutrophil extracellular traps (NETs) result in damage to airway tissue, contributing to the progression of lung disease. Bacterial pathogens are a major driver of airway neutrophilic inflammation, but traditional management of infections with antibiotic therapy is becoming less effective as rates of antimicrobial resistance rise. Bacteriophages (phages) are now frequently identified as antimicrobial alternatives for antimicrobial resistant (AMR) airway infections. Despite growing recognition of their bactericidal function, less is known about how phages influence activity of neutrophils recruited to sites of bacterial infection in the lungs. In this review, we summarize current in vitro and in vivo findings on the effects of phage therapy on neutrophils and their inflammatory mediators, as well as mechanisms of phage-neutrophil interactions. Understanding these effects provides further validation of their safe use in humans, but also identifies phages as a targeted neutrophil-modulating therapeutic for inflammatory airway conditions.